Protein Kinase CK2. - Pinna, Lorenzo A. (Wiley-IUBMB series on biochemistry and molecular biology., 2012)
The importance of CK2 in cancer and other diseases has generated a significant amount of literature on the protein, and an international community of CK2 researchers. The International Union of Biochemistry and Molecular Biology (IUMBMB) sponsors periodic international conferences on CK2, making the protein a natural topic for a Wiley-IUBMB publication. Protein Kinase CK2 will deal with structural aspects underlying the constitutive activity of CK2, its specific susceptibility to pharmacological inhibition and its extraordinary pleiotropy. In the second part the fundamental role of CK2 in a w.